PEMERIKSAAN EMPIRIS PADA PENGARUH KINERJA SOSIAL TERHADAP PROFITABILITAS DI BANK SYARIAH - Muslikhin Muslikhin; Risma Ayu Kinanti; Ridan Muhtadi; Moh. Fudholi (Ulumuna: Jurnal Studi Keilsman, 2020)
Islamic banking is growing rapidly, especially Malaysia, Indonesia, and Brunei Darussalam. This causes Islamic banking to be demanded to be more responsive to stakeholders. This then becomes the basis that Islamic banking must improve its social performance. Social performance is a form of corporate social responsibility to fulfill obligations that come from people's expectations of company behavior. Researchers are interested to find out whether there is an influence of disclosure of social performance on profitability in Islamic banks in Indonesia. This type of research is quantitative using secondary data and linear regression as a data analysis method. This study shows that there is an influence of disclosure of social performance on profitability of Islamic banks in Indonesia.